2014
DOI: 10.1021/ma501630g
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Effects on Glass Transition and Free Surface Viscoelasticity of Ultrathin Polystyrene Films

Abstract: We describe results from experiments in which spontaneous embedment of 20 nm silica particles was used to probe under-layer effects on the free surface dynamics and the glass transition temperature (T g ) of polystyrene. Both 13 and 20 nm thick polystyrene (PS) films were prepared and placed on different under-layer substrates, which in turn were supported on a silicon wafer (Si) substrate. The under-layer substrates used were PS, poly(2-vinylpyridine) (P2VP), and poly(methyl methacrylate) (PMMA) with thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 91 publications
(319 reference statements)
2
45
0
Order By: Relevance
“…The T g of thin films, defined by a simple nanoconfined physical model, has been characterized by different types of measurements, including dynamic, thermodynamic, and pseudothermodynamic (see subsequently for the definitions). In addition, it can also be obtained by investigating the thin film rheological behavior …”
Section: Glass Transition For Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The T g of thin films, defined by a simple nanoconfined physical model, has been characterized by different types of measurements, including dynamic, thermodynamic, and pseudothermodynamic (see subsequently for the definitions). In addition, it can also be obtained by investigating the thin film rheological behavior …”
Section: Glass Transition For Polymersmentioning
confidence: 99%
“…In addition, it can also be obtained by investigating the thin film rheological behavior. [101][102][103][104][105][106][107][108][109][110][111] In general, there are two main factors that contribute to the nanoconfinement of free-standing films, the finite-size effect of a polymer chain and the interface or free surface effect. The finite size effect is related to the diminishing degree of entanglements as a polymer film approaches a thickness of similar size scale to the polymer chain end-to-end distance.…”
Section: Nanoconfinement Effectmentioning
confidence: 99%
“…Over two decades of study on such so-called confined systems have demonstrated that interfaces perturb the local properties not only at the interface, but that the disturbance propagates into the material away from the interface for some distance. [8][9][10][17][18][19][20][21][22][23][24][25] Different types of material properties, glass transition temperature (T g ), [17,[26][27][28] modulus, [13,[29][30][31][32] viscous flow, [33][34][35][36] and physical aging, [18,19,37] have all been reported to change near interfaces and in thin films. Additives distance z ≈ 225-250 nm before bulk PS T g is recovered, while rubbery PS next to glassy polysulfone (PSF) or poly(methyl methacrylate) (PMMA), or rubbery PnBMA next to glassy PS, requires z ≈ 100-125 nm before T g bulk is recovered.…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing the thickness of thin films below 10 nm, the physical and chemical properties of ultrathin films are significantly different in comparison with thin films due to the thickness confinement effect [1315]. To explore such a thickness-dependent effect, a great deal of effort has been devoted to investigating the molecular mobility and relaxation dynamics within ultrathin polymer films [14, 1618]. Previous studies have revealed that the surface relaxation dynamics in ultrathin films were apparently different from that in bulk materials and normal thin films [19, 20].…”
Section: Introductionmentioning
confidence: 99%